1999
DOI: 10.1103/physrevlett.83.5238
|View full text |Cite
|
Sign up to set email alerts
|

ΣHyperons in the Nucleus

Abstract: A search for S hypernuclear states in p-shell hypernuclei has been performed with the Moby Dick spectrometer and the low energy separated beam (LESB-2) at the Brookhaven Alternating Gradient Synchrotron (BNL AGS). Unlike some previously published reports, no narrow states have been observed for targets of 6 Li and 9 Be in ͑K 2 , p 6 ͒ reactions, either for bound state or continuum regions. Together with the previously reported J 0, T 1͞2 bound state in 4 S He, these results demonstrate the crucial role of isos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
105
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 16 publications
(7 reference statements)
8
105
0
Order By: Relevance
“…Namely, the binding energies of Λ can be well-Σ-nucleus potential (Lane term) [12]. The existence of the Lane term was also suggested in light nuclear systems from the systematic difference between the inclusive (K − ,π ± ) spectra [10]. All of the other experiments could not find any bound Σ-hypernuclear state, and failed to give any significant constraint on the Σ-nucleus potential.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the binding energies of Λ can be well-Σ-nucleus potential (Lane term) [12]. The existence of the Lane term was also suggested in light nuclear systems from the systematic difference between the inclusive (K − ,π ± ) spectra [10]. All of the other experiments could not find any bound Σ-hypernuclear state, and failed to give any significant constraint on the Σ-nucleus potential.…”
Section: Introductionmentioning
confidence: 99%
“…1 H) as 1.6M eV respectively. Search for heavier Σ hypernuclei has been carried out by several authors [6], [8], [9], [10], [11], [36] without success. P. K. Saha et al studied inclusive (π − , K + ) spectra on C, Si, Ni, In and Bi targets and concluded that a Σ-nucleus potential is strongly repulsive in such relatively heavy nuclei [6].…”
mentioning
confidence: 99%
“…Further, the crossover density ρ co , where V Ξ − (ρ B = ρ co )=0, is taken to be equal to that for the Λ [52]. As for the V Σ − , recent (K − , π ± ) experiment at BNL [79] suggests a strong isospin dependence in the Σ-nucleus potential. It has been shown that the experimental data is compatible with the analysis by the Nijmegen model F for the baryon-baryon interaction, which gives a repulsive isoscalar part and a large positive isospin dependent term (Lane potential) for the Σ-nucleus potential [78].…”
Section: Potential Contributionmentioning
confidence: 99%